COMPUTER MODELING OF TAXATION - V. Lebedev; K. Lebedev; T. Tyupikova (Вестник университета)
One of the variants of the mathematical model of a single-product enterprise with taxation, which takes into account tax evasion when increasing the tax burden has been considered in the article. The function of profit of the enterprise before the taxation, function of net profit, fiscal function, function of profitability and some other functions, the argument of which is the average tax rate, have been constructed. The constructed model adequately reflects the mechanisms that affect both the production activity of the economic system and the change in state income from taxation. According to model cal-culations, it has shown in particular that the fiscal function of the enterprise can have a maximum point (Laffer point).